Pendugaan Luas Daun Tanaman Talas (Colocasia esculenta) - Yusi Nurmalita Andarini; Higa Afza; Sutoro Sutoro (Institut Pertanian Bogor, 2020)
Estimation of leaf area by using leaf length and leaf width variables could be done without destruction of the leaves from plants and more practical than using the leaf areameter. Surface area is a function of the variable length and width, so the leaf area can be measured based on leaf length and leaf width variables. The purpose of this research is to get the leaf area estimator model with nondestructive method. Taro plants were observed by using 12 accessions/varieties taken from the germplasm collection in Gene Bank Collection of ICABIOGRAD, IAARD. Observations of the length, width, and area of leaf were carried out on 10-12 leaf samples for each accession/variety from taro cultivation which was about 4 months old. The length (P), width (L), and area (Y) of each taro leaf were measured. The estimation of taro leaves area by regression equation was analyzed by using one (P or L) and two (P and L) independent variables. Estimation using two variables, leaf length and width, is better than only use one variable. Taro leaf area (Y) of each leaf can be determined by the equation Y = 0.9462 P x L for ratio of P/L less than 1.10, Y = 0.9109 P x L for ratio of P/L between 1.10-1.19, and Y = 0.8860 P x L for ratio of P/L equal or greater than 1.20. Keywords: model estimation, leaf area, taro